Slow Progression of Cognitive Dysfunction of Alzheimer’s Disease in Sexagenarian Women with Schizophrenia - Kazuo Sakai; Haruhiko Oda; Akira Terashima; Kazunari Ishii; Kiyoshi Maeda (Case Reports in Psychiatry)
Although both schizophrenia (SCZ) and Alzheimer’s disease (AD) are among the most common psychiatric diseases, the interaction of these two is not well-understood. We investigated three women with SCZ who developed AD in their 60s. The patients presented with cognitive dysfunction such as loss of recent memory, which was confirmed by both clinical observations and neuropsychological tests. Their magnetic resonance and functional imaging findings were consistent with AD. Their brain atrophy advanced significantly during a 6-year observation period. However, their global cognitive function did not deteriorate significantly during this period. Although the cognitive reserve model might account for this discrepancy, our results suggest some interactions between the neuropathology of SCZ and AD and warrant further research.